Activity of granulomatosis with polyangiitis and its correlation with mTOR phosphoproteomics in neutrophils - Surmiak, Marcin; Wawrzycka-Adamczyk, Katarzyna; Kosałka-Węgiel, Joanna; Włudarczyk, Anna; Sanak, Marek; Musiał, Jacek (Frontiers in Immunology, 2023)
Introduction. Granulomatosis with polyangiitis (GPA) is a small vessel vasculitis with a complex pathomechanism. Organ damage in GPA is mediated also by extracellular trap formation (NETosis). We analyzed a functional status of phosphoproteins modulating NETosis in neutrophils by mammalian target of rapamycine (mTOR) pathway in GPA along with NETosis biomarkers. Methods. Phosphoproteins levels measured in isolated neutrophils from 42 GPA patients, (exacerbation n=21; remission n=21) and 21 healthy controls were compared to serum biomarkers of the disease. Results. Neutrophils in active disease manifested lowered levels of phosphorylated mTOR (Ser2448) , PTEN (Ser380) and ULK1 (Ser555) , whereas phosphorylated GSK-3α/β (Ser21/Ser9) was elevated. Exacerbation of GPA was characterized by elevated neutrophil dsDNA in serum, circulating mitochondrial DNA and DNA-MPO complexes. A significant negative correlation between mTOR or PTEN phosphoproteins and biomarkers of GPA activity was also present, reflecting the clinical activity score of GPA. Positive correlations between phosphorylated of GSK-3 α/β and circulating mtDNA, DNA-MPO complexes, neutrophil-released dsDNA or circulating proteins were also significant. Increased serum levels of IGFBP-2, TFF-3, CD147, and CHI3L1 accompanied GPA exacerbation, whereas DPP-IV levels were the lowest in active GPA. Using a principal component analysis basigin, PTEN and mTOR had the highest loadings on the discrimination function allowing classification between active, remission and control subjects with 98% performance. Conclusions. We present evidence that inhibited mTOR signaling accompanies NETosis in patients with GPA. The functional status of phosphoproteins suggests simultaneous activation of NETosis and autophagy. These results prompt for studying autophagy as a mechanism underlying granuloma formation in GPA.